Ionization Constants and Partition Coefficient of Some Antiinflammatory Agents in Non-Aqueous Nedia - PEKCAN ERTOKUS, GUZIDE; HAKAN AKTAS, A. (Asian Journal of Chemistry, 2010)
In present study, four antiinflammatory agents, namely naproxen, indomethacin, ibuprofen and etodolac were titrated potentiometrically using tetrabuthylammonium hydroxide in acetonitrile and 2-propanol solvents under nitrogen atmosphere at 25 ºC. The ionization contants of several non-steroidal antiinflammatories have been determined potentiometrically in a series of acetonitrile. Four antiinflammatory agents are non-steroidal antiinflammatory drugs of the family of carboxylic weak acids. The results are compared with octanol-water media. Acetonitrile has a relatively high dielectric constant (ε = 36) and a small autoprotolysis constant (pKs = 33.6). Acetonitrile is higher dielectric constant than octanol. Because of this reason, ionization constant in acetonitrile is lower than in octanol-water mixtures.